A DETERMINANTS OF JOB SATISFACTION TO IMPROVE SAMSAT BALIKPAPAN EMPLOYEE PERFORMANCE - Hasan, Syahril; Novitasari, Wiwik; Kardinar Wijayanti, Silvana (Universitas Muhammadiyah Kalimantan Timur, 2024)
This study aimed to determine whether influential factors such as leadership, work culture, compensation, and job performance simultaneously and partially affect the job satisfaction of SAMSAT Balikpapan employees. This study used a population of 54 respondents using multiple linear regression test method with SPSS tool version 25. Hypothesis Analysis and Testing Techniques using Validity and Reliability Tests. Use Concurrent and Partial tests and the Classical Assumptions test. The results showed that leadership, work culture, and work performance simultaneously positively and significantly affected the job satisfaction of SAMSAT Balikpapan employees. In comparison, compensation has a negative and insignificant influence on job satisfaction. Work culture has a significant and partly dominant effect on SAMSAT Balikpapan job satisfaction. Regression results satisfy the classical assumption that there is no multicollinearity and no autocorrelation. This field contribution causes the Company to pay more attention to compensation variables to increase employee satisfaction. Work culture has a significant and dominant influence on job satisfaction but needs attention to job compensation.